2014
DOI: 10.1002/rcr2.47
|View full text |Cite
|
Sign up to set email alerts
|

D ieulafoy's disease of the bronchus: a rare cause of massive hemoptysis

Abstract: We present the case of a 30-year-old non-smoker who presented with unexplained, massive hemoptysis and was diagnosed with a rare vascular malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In the absence of an obvious cause, it seems reasonable to assume that the lesion is congenital. Smith et al speculated that the disease arises from a failure of a caliber-persistent artery running within the submucosa to differentiate into capillaries [5]. When the right side is involved, Stoopen's theory of avaried embryologic development of the right bronchial artery leading to a higher risk for right anomalous vessels points towards a congenital etiology [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of an obvious cause, it seems reasonable to assume that the lesion is congenital. Smith et al speculated that the disease arises from a failure of a caliber-persistent artery running within the submucosa to differentiate into capillaries [5]. When the right side is involved, Stoopen's theory of avaried embryologic development of the right bronchial artery leading to a higher risk for right anomalous vessels points towards a congenital etiology [2].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases were reported from Asia (38 patients) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], followed by Europe (23 patients) [3,4,[25][26][27][28][29][30][31][32][33][34][35][36][37], North America (seven patients) [38][39][40][41][42][43][44], Oceania (two patients) [5,45], and the country of origin was not reported for three patients (Fig. 2) [46].…”
Section: Continent and Country Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…It will usually make it possible to find both the source and the cause of the bleeding. 3 The characteristics of the lesion are nonspecific, but it can be suspected when a small (usually less than 1 cm) sessile non-pulsatile nodular lesion with a white cap and apparently normal mucosa is seen. 2 It has been suggested that, after the diagnosis has been made, angiography and embolization can be the preferred treatment 5,6 and that surgical resection would only be needed in a few cases.…”
Section: 3mentioning
confidence: 99%
“…[ 2 ] Dieulafoy disease of the bronchus is considered a congenital anomaly and it is speculated that the disease arises from a failure of caliber-persistent artery running within the submucosa to differentiate into capillaries. [ 3 ] The dilated tortuous arteries in the submucosa originate from the bronchial artery and pulmonary artery and are vulnerable to bleeding.…”
Section: Introductionmentioning
confidence: 99%